Research trends and hotspots of glial fibrillary acidic protein within the area of Alzheimer’s disease: a bibliometric analysis - Zou, Yutong; Li, Lei; Guan, Lihua; Ma, Chaochao; Yu, Songlin; Ma, Xiaoli; Mao, Chenhui; Gao, Jing; Qiu, Ling (Frontiers in Aging Neuroscience, 2023)
Objective Our aim was to analyze the trends and hotspots on glial fibrillary acidic protein (GFAP) within the area of Alzheimer’s disease (AD) by using a bibliometric method, which is currently missing. Methods All articles and reviews on GFAP within the area of AD from inception to December 31, 2022, were searched from the Web of Science Core Collection. Full records were derived, imported into Microsoft Excel, and analyzed by BIBLIOMETRC, VOSviewer, and CiteSpace. Results In total, 2,269 publications, including 2,166 articles, were ultimately included. The number of publications from 81 countries/regions and 527 academic journals increased annually. The top three prolific countries and institutions were the USA, China, and England, the University of Gothenburg (Sweden), Federal University of Rio Grande do Sul (Brazil), and UCL Queen Square Institute of Neurology (England). Henrik Zetterberg from the University of Gothenburg, Kaj Blennow from the University of Gothenburg, and Alexei Verkhratsky from the University of Manchester were the top three prolific and cited authors; Journal of Alzheimer’s Disease, Brain Research, and Neuroscience contributed the most publications. The top key areas of research included “molecular, biology, and genetics” and “molecular, biology, and immunology,” and the top published and linked meaningful keywords included oxidative stress, inflammation/neuroinflammation, microglia, hippocampus, amyloid, cognitive impairment, tau, and dysfunction. Conclusion Based on the bibliometric analysis, the number of publications on GFAP within the area of AD has been rapidly increasing, especially in the past several years. Oxidative stress and inflammation are research hotspots, and GFAP in body fluids, especially blood, could be used for large-scale screening for AD.